On the optimality of serial and parallel processing in the psychological refractory period paradigm: Effects of the distribution of stimulus onset asynchronies. - Miller, Jeff; Ulrich, Rolf; Rolke, Bettina (Cognitive Psychology, 2009)
Within the context of the psychological refractory period (PRP) paradigm, we developed a general theoretical framework for deciding when it is more efficient to process two tasks in serial and when it is more efficient to process them in parallel. This analysis suggests that a serial mode is more efficient than a parallel mode under a wide variety of conditions and thereby suggests that ubiquitous evidence of serial processing in PRP tasks could result from performance optimization rather than from a structural bottleneck. The analysis further suggests that the experimenter-selected distribution of stimulus onset asynchronies (SOAs) influences the relative efficiency of the serial and parallel modes, with a preponderance of short SOAs favoring a parallel mode. Experiments varying the distribution of SOAs were conducted, and the results suggest that there is a shift from a more serial mode to a more parallel mode as the likelihood of short SOAs increases. Copyright (c) 2009 Elsevier Inc.